Volterra Runge- Kutta Methods for Solving Nonlinear Volterra Integral Equations - Baghdad Science Journal (مجلة بغداد للعلوم)
In this paper Volterra Runge-Kutta methods which include: method of order two and four will be applied to general nonlinear Volterra integral equations of the second kind. Moreover we study the convergent of the algorithms of Volterra Runge-Kutta methods. Finally, programs for each method are written in MATLAB language and a comparison between the two types has been made depending on the least square errors.